The development and effects of Tariro Youth drug abuse intervention module (TYDAIM) on self-concept in Zimbabwe - Maraire, Tariro (2023)
In recent years, Zimbabwe has been grappling with the problem of drug abuse particularly among the youth. The situation has been exacerbated by the scarcity in appropriate treatments for drug abuse in Zimbabwe. Hence, this study developed and tested the effects of Tariro Youth Drug Abuse Intervention Module (TYDAIM). This module is guided by Christian Psychology, Christian Cognitive Behavioural Therapy (CCBT) and the Bible, which focuses on self-control and self-concept enhancement. The study utilised a mixed approach, where “design based research” was employed for the module development and quasi-experimental method for the module testing. The TYDAIM was validated by eight experts in the fields related to the current study. A pilot study on 34 participants was conducted to test the adequacy of the study’s research instruments. Effects of the TYDAIM were tested on 56 youth drug abusers at a youth centre in Chitungwiza, Zimbabwe using ANCOVA. The Brief Self-Control Scale and the Personal Self-Concept Scale were used to measure self-control and selfconcept levels of participants in both pre and post-test. Results from the study showed a significant effect of the TYDAIM intervention on post-test self-control results after controlling for pre-test, F (1, 52) = 0.790, p ˂ 0.05, with a large effect size Cohen’s d = 0.82. The study results also showed that there is a significant effect of the TYDAIM intervention on post-test self-concept results after controlling for pre-test, F (1, 52) = 1.115, p ˂ 0.05, whilst controlling for pre-test levels, with a small effect size Cohen’s d = 0.21. Data also showed that there is a strong positive correlation between selfcontrol and self-concept, r (54) = .92, p ˂ 0.001. The study concludes that the TYDAIM can be utilised to affect change among drug abusers. The study also recommends for future studies to use the module on a broader scale so that findings could be generalized to the entire drug abusers’ population in Zimbabwe.